Effects of islet transplantation on microvascular and macrovascular complications in type 1 diabetes. Issue 7 (3rd May 2021) - Reid, Laura; Baxter, Faye; Forbes, Shareen
Abstract: Type 1 diabetes is associated with high morbidity and mortality from microvascular and macrovascular disease with considerable economic cost to society. Islet cell transplantation (ICT) is a treatment option recommended by National Institute for Health and Care Excellence (NICE) for people with debilitating hypoglycaemia due to type 1 diabetes, including those with renal failure where kidney transplantation may also be indicated. The primary aim of ICT is to improve glycaemic control, reduce severe hypoglycaemia, stabilise glycaemic variability and restore awareness of hypoglycaemia where this is compromised. Insulin independence, although not a primary aim, should also be considered a therapeutic goal. The impact ICT has on the progression of microvascular and macrovascular diabetes complications is derived from small studies and has not been examined in large clinical trials. Lifelong immunosuppression, which is necessary to avoid transplant rejection, has adverse effects on lipid metabolism, hypertension and renal function, which must also be considered. In this review, we discuss the role of ICT in type 1 diabetes management and the available evidence with respect to microvascular and macrovascular disease progression post‐transplantation. We conclude that, following ICT, microvascular complications including retinopathy and neuropathy are stabilised or improved. Effects on nephropathy can be complicated by coexisting kidney transplantation and the impact of immunosuppression, the latter leading to an early decline in renal function; however, there is evidence to suggest stable renal outcomes in the long term. Short‐term studies have demonstrated a positive impact of ICT on surrogate markers of macrovascular disease; however, long‐term studies and trials in this area are lacking.